The Indian Rape Law: Vocabulary of Protest, Reactionary Legislations and Quality of Equality Culture - Shruti Bedi (Udayana Journal of Law and Culture, 2023)
The problem of violence perpetrated against women in India is not simple. It is embroiled in the historical subjugation of the ‘weaker sex.’ Women have been unable to claim equality in society despite mandatory provisions in the Constitution of India and other legislations in their favour. Despite numerous amendments to the Indian criminal law, rape, one of the most heinous crimes, continues to be committed in India at an alarming rate. The law on Rape in India has undergone three phases of amendments, and all precipitated in the aftermath of public fury on account of brutal and heinous incidents of rape. This paper employs the socio-legal approach to assess the efficacy and impact of these amendments in changing social behaviour. It concludes that though the massive public outrage undoubtedly led to radical amendments, it was a knee-jerk reaction that suffered from legislative ambiguities. The increase in the retributive content of the law ultimately resulted in reduced convictions. Although law is believed to be an instrument of social change, the amendments in the anti-rape legislation have been unable to bring about a positive transformation in the existing cultural inequality.